2015
DOI: 10.1152/jn.00408.2014
|View full text |Cite
|
Sign up to set email alerts
|

Cholinergic systems are essential for late-stage maturation and refinement of motor cortical circuits

Abstract: Ramanathan DS, Conner JM, Anilkumar AA, Tuszynski MH. Cholinergic systems are essential for late-stage maturation and refinement of motor cortical circuits. J Neurophysiol 113: 1585-1597, 2015. First published December 10, 2014 doi:10.1152/jn.00408.2014.-Previous studies reported that early postnatal cholinergic lesions severely perturb early cortical development, impairing neuronal cortical migration and the formation of cortical dendrites and synapses. These severe effects of early postnatal cholinergic les… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 106 publications
0
14
0
Order By: Relevance
“…; Ramanathan et al . ). However, these experiments mostly relied on the deletion of specific nAChR subtypes or on disruption of cholinergic inputs to the target cells which in both cases reduces cholinergic signalling.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…; Ramanathan et al . ). However, these experiments mostly relied on the deletion of specific nAChR subtypes or on disruption of cholinergic inputs to the target cells which in both cases reduces cholinergic signalling.…”
Section: Discussionmentioning
confidence: 97%
“…To our surprise the pruning of excitatory inputs to VNLL neurons was not diminished in nicotine-treated mice. A direct link between nAChRs and synaptic remodelling has been suggested for a number of cortical neural circuits (Liu et al 2007;Lozada et al 2012;Ramanathan et al 2015). However, these experiments mostly relied on the deletion of specific nAChR subtypes or on disruption of cholinergic inputs to the target cells which in both cases reduces cholinergic signalling.…”
Section: Nachr Activation May Directly Modulate Synaptic Transmissionmentioning
confidence: 99%
“…More recently, the key role of acetylcholine in motor skill learning has been more closely investigated. Indeed, acetylcholine modulates the reorganization of cortical maps following motor training (Conner et al, 2003 , 2010 ; Ramanathan et al, 2009 , 2015 ). Moreover, muscarinic receptors have been shown to be involved in motor cortex activity and plasticity (Desai and Walcott, 2006 ; Tian et al, 2014 ; Hedrick and Waters, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…The sites of motor computations appear to be distributed across many areas of the CNS, making it challenging to identify the origin of body part-specific movements. Microstimulation and anatomical studies have shown that higher-level (supraspinal) circuitry contributes to the computations necessary to generate motor commands appropriate for particular body segments (Esposito et al, 2014;Graziano et al, 2002;Harrison et al, 2012;Jeffery and Fitzgerald, 1999;Ramanathan et al, 2015;Tennant et al, 2012). In addition to supraspinal structures, the spinal cord itself is a major site for computing motor actions at each level of the body (Bizzi et al, 1991;H€ agglund et al, 2013;Juvin et al, 2005;Levine et al, 2014;Ruder et al, 2016).…”
Section: Introductionmentioning
confidence: 99%